THE EFFECT OF PRODUCT QUALITY, PRICE AND DISTRIBUTION ON THE PURCHASE DECISION OF AVIATOR BRAND BIKE (Survey of Bike Shops in Bangkinang City) - Andriano Andriano; Arman Arman; Azhari Azhari; Royansyah Putra (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of product quality, price and distribution simultaneously and partially on the purchasing decision of bike aviator (Survey at a bicycle shop in Bangkinang city). The types and sources of data used in this study are primary data and secondary data, while the data collection technique is using questionnaires, research files, observations, the analysis used in this study is multiple linear analysis with a sample of 100 people. The sample collection technique is by using accidental sampling technique. Based on the results of simultaneous tests, product quality, price and distribution variables have a joint effect on purchasing decisions for aviator brand bicycles (a survey at bicycle shops in Bangkinang Kota), while based on a partial test, product quality, price and distribution variables have been shown to have a significant effect on their own. -self to the decision to purchase an aviator brand bicycle (a survey at a bicycle shop in Bangkinang City, the closeness of the relationship that occurs between the variables of product quality, price and distribution on purchasing decisions is very strong. Meanwhile, the contribution of the independent variable to the dependent variable is 78.90%